2009
DOI: 10.1074/jbc.m806461200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of APC/C-E3 Ligase with Swi6/HP1 and Clr4/Suv39 in Heterochromatin Assembly in Fission Yeast

Abstract: Heterochromatin assembly in fission yeast is initiated by binding of Swi6/HP1 to the Lys-9-dimethylated H3 followed by spreading via cooperative recruitment of Swi6/HP1. Recruitment of Cohesin by Swi6/HP1 further stabilizes the heterochromatin structure and integrity. Subsequently, polyubiquitylation of Cut2 by anaphase-promoting complexcyclosome (APC/C)-ubiquitin-protein isopeptide ligase (E3 ligase) followed by degradation of Cut2 releases Cut1, which cleaves the Rad21 subunit of Cohesin, facilitating sister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 53 publications
0
17
1
Order By: Relevance
“…Further, the swi6 -115 mutant does express a drastically reduced albeit detectable level of Swi6 (23), whereas the swi6⌬ mutant does not. Thus, earlier results may have had a contribution from the residual Swi6 in initiating the heterochromatin mark by recruiting Clr4, whereas the lack of Swi6 in the present study and our previous study (26) implies a complete lack of Clr4 recruitment in the swi6⌬ mutant, leading to a defect in both establishment and maintenance of heterochromatin.…”
Section: Swi6 Exists As a Tetramer In Vivo-whethercontrasting
confidence: 52%
“…Further, the swi6 -115 mutant does express a drastically reduced albeit detectable level of Swi6 (23), whereas the swi6⌬ mutant does not. Thus, earlier results may have had a contribution from the residual Swi6 in initiating the heterochromatin mark by recruiting Clr4, whereas the lack of Swi6 in the present study and our previous study (26) implies a complete lack of Clr4 recruitment in the swi6⌬ mutant, leading to a defect in both establishment and maintenance of heterochromatin.…”
Section: Swi6 Exists As a Tetramer In Vivo-whethercontrasting
confidence: 52%
“…Prior work has demonstrated that the maintenance of centromeric heterochromatin is necessary for proper chromosomal segregation during mitotic progression in both S. pombe (28) and human cells (29), and regulation of expression of alphoid transcripts is required for mitosis (49). Since both centromeric alphoid regions and transposable elements are maintained in a heterochromatic state during mitosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In S. pombe (28) and C. elegans (5,6), the recruitment of RITS to heterochromatic regions requires the synthesis of dsRNAs and processing to siRNAs. To assess hTERT-associated RdRP activity, we established an IP-RdRP assay by modifying a method used to analyze the C. elegans RdRP (21).…”
Section: Htert Localizes To Both Mitotic Spindles and Centromeresmentioning
confidence: 99%
See 1 more Smart Citation
“…This would provide a molecular mechanism to explain how the APC controls lifespan and how the cell overcomes Fob1's potential negative effects on rDNA recombination and longevity. Recent work has demonstrated that the APC is required for rDNA silencing, assembly, and segregation in budding and fission yeast (Sullivan et al 2008;Dubey et al 2009;Rodríguez-Sánchez et al 2011). Thus, the identification of Fob1 as a novel APC target would provide insight into how the APC may influence rDNA biology.…”
mentioning
confidence: 99%